Sanctuary of support a palliative care facility for breast cancer patients and care providers through therapeutic architecture - Galang, Joan F. (College of Architecture, University of the Philippines Diliman, 2025)
In the realm of building sciences, there has been a continued effort to lay the groundwork for the practical application of therapeutic architecture, allowing for significant improvements in the quality of life, health, and overall well-being of patients in a hospital setting. This study aims to combine the framework of palliative care with spatial parameters of therapeutic architecture to yield an evidence-based design of a healing environment for breast cancer patients and family caregivers. A site within Batangas City was selected as the location of a proposed palliative care healthcare facility for breast cancer patients and family caregivers. The roles of various stakeholders in the proposed facility were analyzed, resulting in an activity program of three indicated user groups. Spatial analysis and programming were formulated from the technical review of pertinent standards and guidelines. Furthermore, five zones were synthesized according to their function: outer, consultative, curative, therapeutic, and service zone. Research findings revealed three overarching study focuses: (1) humanization of spaces, (2) holistic palliative care process, and (3) therapeutic environment design, which were applied as core architectural concepts of the design process for the proposed palliative care facility.In the realm of building sciences, there has been a continued effort to lay the groundwork for the practical application of therapeutic architecture, allowing for significant improvements in the quality of life, health, and overall well-being of patients in a hospital setting. This study aims to combine the framework of palliative care with spatial parameters of therapeutic architecture to yield an evidence-based design of a healing environment for breast cancer patients and family caregivers. A site within Batangas City was selected as the location of a proposed palliative care healthcare facility for breast cancer patients and family caregivers. The roles of various stakeholders in the proposed facility were analyzed, resulting in an activity program of three indicated user groups. Spatial analysis and programming were formulated from the technical review of pertinent standards and guidelines. Furthermore, five zones were synthesized according to their function: outer, consultative, curative, therapeutic, and service zone. Research findings revealed three overarching study focuses: (1) humanization of spaces, (2) holistic palliative care process, and (3) therapeutic environment design, which were applied as core architectural concepts of the design process for the proposed palliative care facility.